Challenges and opportunities for women entrepreneurs in the renewable energy sector across the MENA region for sustainable development - Zakzouk, Fida; Bandarra Filho, Enio P.; Farooq, Muhammad (Frontiers in Sustainability, 2025)
This research explores both the challenges and prospects faced by women entrepreneurs operating in the renewable energy sector within six MENA countries: Saudi Arabia, Egypt, Jordan, Morocco, Qatar, and Tunisia. Drawing from 120 survey responses alongside an extensive review of existing literature, the study uncovers a complex landscape where gender-based obstacles persist. This happens due to cultural backgrounds, flaws within the system and restricted opportunities to build good relationships in the field. In spite of that, many women entrepreneurs have remarkable adaptability, in many cases relying on informal channels and their individual coping abilities to navigate these structural barriers. It is also evident from the analysis that North African countries tend to offer better opportunities than Gulf States. A new sustainable conceptual framework, the “glass grid,” is proposed to capture the sector’s unique horizontal barriers that limit women’s participation in the field and career progression. This study proposes tailored policy recommendations that include gender-responsive finances, regular mentoring, and shifts in culture in addition to increased collaborations across the region for sustainable development. Involving women in renewable energy sector is seen as necessary for achieving equality, advancing sustainability and progress in innovation in the MENA region.